VIOLENCE AS RESOLUTION IN CINEMA NARRATIVE A STUDY OF MALAYALAM CINEMA SINCE THE INCEPTION OF FILM AWARDS BY THE GOVERNMENT OF KERALA - Shanthi Mathai (Mass Communicator, 2015)
Cinema as a motion picture medium with proper sound effects has the potential to provide maximum entertainment value to the audience. Story narratives are one of the key elements in the success of any movie and violence in different forms play important roles in completing the story and its impact. Socio-economic, political and cultural changes as well as developments in the field of science and technology have changed the world and the lifestyle of people in numerous ways, in the last 50 years. If cinema reproduces human society and its virtues through the stories, how much of these changes get reflected in the cinema? Has the cinema changed substantially during this period? The assumption of this study is that the changes should be mirrored in the story including the depiction of violence in the movies. It explores the differences in sketching the resolution of violence and vulnerability in the 3 rd act of movies by analyzing selected movies of the last 50 years. Selection of sample is done from the Malayalam movies those which received the Kerala State award. The study analyses the presence of violence in the three different ‘Acts’ of the movie narratives and use of violence as a resolution.